Respuestas
Respuesta dada por:
0
1) f(p) = 4/p; g(p) =(p - 2)/3
(f o p) = 4/(p - 2)/3 = 4x3/(p - 2) = 12/p - 2
2.) I(u) = (1000 - 2U).U = 1000U - 2U²
I(100) = 1000(100) - 2(100²) = 100000 - 20000 = 80000
3.)
g(x) = 4x + 3
f(g(x)) =![50+ \sqrt{ \frac{4x+3}{150}} 50+ \sqrt{ \frac{4x+3}{150}}](https://tex.z-dn.net/?f=50%2B+%5Csqrt%7B+%5Cfrac%7B4x%2B3%7D%7B150%7D%7D+)
4.) G(t) = 40 - 2t:
G - 40 = -2t
-G/2 - (40/-2) = t
20 - (G/2) = t
5.)
![g(X)= \frac{2}{X+2} g(X)= \frac{2}{X+2}](https://tex.z-dn.net/?f=g%28X%29%3D+%5Cfrac%7B2%7D%7BX%2B2%7D+)
(f+g)(2)
![2\sqrt{X-1}+ \frac{2}{X+2}= \frac{(X+2)(2\sqrt{X-1})+2}{X+2} 2\sqrt{X-1}+ \frac{2}{X+2}= \frac{(X+2)(2\sqrt{X-1})+2}{X+2}](https://tex.z-dn.net/?f=2%5Csqrt%7BX-1%7D%2B+%5Cfrac%7B2%7D%7BX%2B2%7D%3D+%5Cfrac%7B%28X%2B2%29%282%5Csqrt%7BX-1%7D%29%2B2%7D%7BX%2B2%7D+++)
![(X+2)(2 \sqrt{X-1})=2X\sqrt{X-1}+4\sqrt{X-1} (X+2)(2 \sqrt{X-1})=2X\sqrt{X-1}+4\sqrt{X-1}](https://tex.z-dn.net/?f=%28X%2B2%29%282+%5Csqrt%7BX-1%7D%29%3D2X%5Csqrt%7BX-1%7D%2B4%5Csqrt%7BX-1%7D+)
![(f+g)(x)= \frac{2X\sqrt{X-1}+4\sqrt{X-1}+2}{X+2} (f+g)(x)= \frac{2X\sqrt{X-1}+4\sqrt{X-1}+2}{X+2}](https://tex.z-dn.net/?f=%28f%2Bg%29%28x%29%3D+%5Cfrac%7B2X%5Csqrt%7BX-1%7D%2B4%5Csqrt%7BX-1%7D%2B2%7D%7BX%2B2%7D+)
![(f+g)(2)= \frac{2(2)\sqrt{2-1}+4\sqrt{2-1}+2}{2+2} (f+g)(2)= \frac{2(2)\sqrt{2-1}+4\sqrt{2-1}+2}{2+2}](https://tex.z-dn.net/?f=%28f%2Bg%29%282%29%3D+%5Cfrac%7B2%282%29%5Csqrt%7B2-1%7D%2B4%5Csqrt%7B2-1%7D%2B2%7D%7B2%2B2%7D+)
(f+g)(2)= \frac{4\sqrt{1}+4\sqrt{1}+2}{4}
![(f+g)(2)= \frac{4+4+2}{4} (f+g)(2)= \frac{4+4+2}{4}](https://tex.z-dn.net/?f=%28f%2Bg%29%282%29%3D+%5Cfrac%7B4%2B4%2B2%7D%7B4%7D)
(f+g)(2) = 10/4 = 5/2
6.)
![f(x)= \frac{5000X}{X+100} f(x)= \frac{5000X}{X+100}](https://tex.z-dn.net/?f=f%28x%29%3D+%5Cfrac%7B5000X%7D%7BX%2B100%7D+)
Y(X + 100) = [5000X/(X+100)](X+100)
Y(X + 100) = 5000X
Y(X) + Y(100) = 5000X
5000X = YX + 100Y
5000X - YX = 100Y
-X(Y - 5000) = 100Y
X = 100Y/-(Y -5000)
X = -100Y/(Y - 5000)
X = Y
Y = -100X/(Y - 5000)
![f^{-1}(X) = \frac{-100X}{(Y - 5000)} f^{-1}(X) = \frac{-100X}{(Y - 5000)}](https://tex.z-dn.net/?f=f%5E%7B-1%7D%28X%29+%3D++%5Cfrac%7B-100X%7D%7B%28Y+-+5000%29%7D++)
(f o p) = 4/(p - 2)/3 = 4x3/(p - 2) = 12/p - 2
2.) I(u) = (1000 - 2U).U = 1000U - 2U²
I(100) = 1000(100) - 2(100²) = 100000 - 20000 = 80000
3.)
f(g(x)) =
4.) G(t) = 40 - 2t:
G - 40 = -2t
-G/2 - (40/-2) = t
20 - (G/2) = t
5.)
(f+g)(2)
(f+g)(2)= \frac{4\sqrt{1}+4\sqrt{1}+2}{4}
(f+g)(2) = 10/4 = 5/2
6.)
Y(X + 100) = [5000X/(X+100)](X+100)
Y(X + 100) = 5000X
Y(X) + Y(100) = 5000X
5000X = YX + 100Y
5000X - YX = 100Y
-X(Y - 5000) = 100Y
X = 100Y/-(Y -5000)
X = -100Y/(Y - 5000)
X = Y
Y = -100X/(Y - 5000)
Preguntas similares
hace 7 años
hace 7 años
hace 7 años
hace 9 años
hace 9 años
hace 9 años